2021
DOI: 10.1002/er.7015
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of the photovoltaic‐thermoelectric system combined with serpentine type water collector

Abstract: Summary In this work, performance analysis of the photovoltaic‐thermoelectric with serpentine water collector (PV‐TE‐SWC) has been carried out. For extracting the heat from the back surface of the combined PV‐TE system and to maintain a temperature gradient, a serpentine‐type tube and sheet water collector is proposed. The electrical efficiency of the designed PV‐TE‐SWC is compared with the experimental and theoretical results on a similar type of collector from the literature to validate the proposed simulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Figure 2 presents the finite element optimization results of the hybrid system utilizing cell 1 as the effects of the principal operating parameters on the system performance are investigated. Overall, isolated variations of these parameters are observed to significantly affect the hybrid system performance, as reported in similar previous studies [31,55]. Figures 2(a) and 2(b) depict the effect of concentrated solar irradiance on the system performance.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Figure 2 presents the finite element optimization results of the hybrid system utilizing cell 1 as the effects of the principal operating parameters on the system performance are investigated. Overall, isolated variations of these parameters are observed to significantly affect the hybrid system performance, as reported in similar previous studies [31,55]. Figures 2(a) and 2(b) depict the effect of concentrated solar irradiance on the system performance.…”
Section: Resultssupporting
confidence: 79%
“…It was found that at ambient operating conditions of 37.8 °C and 874 W/m 2 , the proposed system could produce hot water at a capacity of 80 L per day at a heat transfer rate of 535.5 W/day. Gupta et al, [31] conducted the performance analysis of a solar photovoltaic-thermoelectric integrated with a serpentine water collector for removing the waste heat from the back surface of the hybrid system. The performance of the proposed system was compared with 2…”
Section: Introductionmentioning
confidence: 99%
“…These findings show that serpentine collectors produce high thermal performance but minor electrical efficiency enhancement, in line with the results tabulated in Table 3. Another study on serpentine ST-PVT was carried out by Gupta et al [102]. They analyzed numerically a glazed PVT system combined with thermoelectric using weather data from Pune, India.…”
Section: Serpentinementioning
confidence: 99%
“…They analyzed numerically a glazed PVT system combined with thermoelectric using weather data from Pune, India. They found that the serpentine collectors could increase overall Another study on serpentine ST-PVT was carried out by Gupta et al [102]. They analyzed numerically a glazed PVT system combined with thermoelectric using weather data from Pune, India.…”
Section: Serpentinementioning
confidence: 99%
“…However, researchers have proposed several means of cooling the solar panel when exposed to harsh environmental conditions like concentrated solar using active, passive, phase change material, and thermoelectric cooling techniques [11,12]. Among these proposed techniques, the thermoelectric cooling method stands out due to the relative effectiveness, commercial availability, and affordability of the thermoelectric module (TEM) in cooling the concentrated solar photovoltaic (CPV) system [13][14][15]. Some researchers have experimentally demonstrated how the CPV-TE hybrid system was capable of generating a higher power and efficiency than the stand-alone CPV system by utilizing the entire broad solar spectrum [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%